2016
DOI: 10.1016/j.solener.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Control criteria of electrochromic glasses for energy savings in mediterranean buildings refurbishment

Abstract: During the next decades the refurbishment of old buildings will be an essential way to contribute to the global improvement of buildings energy performance indicators. Within this context, the present paper is focused on the use of electrochromic (EC) windows, an emerging technology alternative to shading devices, to control solar gains in buildings located in Mediterranean climates. The optical properties adjustments of the EC glasses are discussed based on the incident solar radiation. The ESP-r building ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 49 publications
0
25
0
3
Order By: Relevance
“…Tavares et al [119,120] demonstrated the usefulness of switchable windows in terms of energy savings in air conditioning for sun-oriented (South, West and East) façades.…”
Section: Effects On Visual Comfort Durability and Life-cycle Assessmementioning
confidence: 99%
“…Tavares et al [119,120] demonstrated the usefulness of switchable windows in terms of energy savings in air conditioning for sun-oriented (South, West and East) façades.…”
Section: Effects On Visual Comfort Durability and Life-cycle Assessmementioning
confidence: 99%
“…However, the drawback of most electrochromic glazing products is their low speed of response. It requires five minutes for a 10 cm × 30 cm glass [18] to be colored, and eight minutes and 12 min for a 1.2 m × 0.8 m glass to be colored and bleached, respectively [19]. On the contrary, a few recently released electrochromic glazing products can be colored within three minutes.…”
Section: Research Background and Objectivementioning
confidence: 99%
“…The key variables in defining this type of control scheme are the optical properties of the intermediate dark states and the insolation thresholds at which the control switches to these states. Additional testing was done to determine the appropriate values of these parameters, which are based in part on control thresholds modeled in previous studies [63]. In these tests, a series of controls are constructed with varying propensities to switch to darker states, i.e.…”
Section: Dynamic Control Strategiesmentioning
confidence: 99%